Observations of Energy Conversion Caused by Magnetic Reconnection at a Dipolarization Front - K. Jiang; S. Y. Huang; Z. G. Yuan; Q. Y. Xiong; S. B. Xu; R. T. Lin (Geophysical Research Letters)
Abstract Dipolarization fronts (DFs) are widely believed to host energy conversion processes. However, which mechanism is responsible for the energy conversion is still obscure. Using data from the Magnetospheric Multiscale mission, a current sheet is observed at a DF. This current sheet is caused by interchange instability bending the edge of the DF. Inside the current sheet, Hall electromagnetic field, super Alfvénic electron jets, demagnetization of ions and electrons, strong energy conversion, and steady ion flow and temperature are observed, indicating an electron‐only reconnection at the DF. The duskward plasma flow, which may be deflected by the DF, compresses the bent edges of the DF. As a result, the width of the current sheet between two adjacent bent edges of the DF reduces, and then reconnection begins. Our observations give direct evidence that magnetic reconnection results in energy conversion at a DF.